2016
DOI: 10.1177/0003319716660245
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a “Weekend Effect” for Renal Transplant Recipients

Abstract: The "weekend (WE) effect" defines the association between WE hospital admissions and higher rate of mortality. The aim of this study was to evaluate the relationship between WE effect and renal transplant recipients (RTRs) using the database of the Emilia-Romagna region (ERR), Italy. We included ERR admissions of RTRs ( International Classification of Diseases, Ninth Revision, Clinical Modification [ ICD-9-CM] code V420) between 2000 and 2013. In-hospital mortality, admissions due to cardiovascular events (CVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Also, an increased alertness of the challenges and difficulties within the medical care system on weekends, in particular regarding the treatment of RTx recipients, might contribute to the comparable outcome between weekday and weekend RTx. The increased sensitivity towards this exceptional cohort of patients was stressed in a recent study by Manfredini et al who showed that RTx recipients are not exposed to a higher risk of adverse outcome when admitted to the hospital on weekends compared to weekdays [ 24 ]. Moreover, patients on the waiting list are usually clinical stable, undergo regular investigations and are repeatedly seen by physicians and health care staff (at least patients on haemodialysis) in contrast to other patients that are admitted on weekends because of acute critical illness and emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, an increased alertness of the challenges and difficulties within the medical care system on weekends, in particular regarding the treatment of RTx recipients, might contribute to the comparable outcome between weekday and weekend RTx. The increased sensitivity towards this exceptional cohort of patients was stressed in a recent study by Manfredini et al who showed that RTx recipients are not exposed to a higher risk of adverse outcome when admitted to the hospital on weekends compared to weekdays [ 24 ]. Moreover, patients on the waiting list are usually clinical stable, undergo regular investigations and are repeatedly seen by physicians and health care staff (at least patients on haemodialysis) in contrast to other patients that are admitted on weekends because of acute critical illness and emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study of the Australia and New Zealand Dialysis and Transplant registry concluded that timing of transplantation did not impact on allograft outcome [ 31 ]. Also, our group tested this hypothesis on all cases of the Emilia-Romagna region, but did not find any risk of adverse outcome related to the WE effect, observing only that WE admissions were characterized by longer duration of hospitalization [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most failures caused by vascular complications occur within the first 7 days post-transplant, leading to short-term transplant failure and long-term reduced patient and graft survival rates. One reason is that the majority of post-kidney transplantation care is ward-based but remains predominantly led by senior medical or surgical reviews all days of the week, possibly shielding kidney allograft recipients from any weekend effect [22]. In addition, there are the most experienced transplant team members who can access vascular imaging services in a timely manner, especially for patients with a large burden of vascular diseases involved in complex vascular/anastomotic transplantation.…”
Section: Plos Onementioning
confidence: 99%